THEORETIC AND METHODOLOGIC BASICS OF DEVELOPMENT OF THE NATIONAL LOGISTICS SYSTEM IN THE REPUBLIC OF BELARUS - R. B. Ivut (Nauka i Tehnika, 2016)
The article presents the results of a study, the aim of which is the formation of the theoretical and methodological foundations in the framework of scientific maintenance for the further development processes of the national logistics system in the Republic of Belarus. The relevance of the study relates to the fact that at present the introduction of the concept of logistics and the formation of the optimal infrastructure for its implementation are the key factors for economic development of Belarus as a transit country. At the same time the pace of development of the logistic activities in the country is currently slightly lower in comparison with the neighboring countries, as evidenced by the dynamics of the country’s position in international rankings (in particular, according to the LPI index). Overcoming these gaps requires improved competitiveness of the logistics infrastructure in the international market. This, in turn, is possible due to the clear formulation and adherence of the effective functioning principles for macro logistics system of Belarus, as well as by increasing the quality of logistics design by means of applying econometric models and methods presented in the article. The proposed auctorial approach is the differentiation of the general principles of logistics specific to the logistics systems of all levels, and the specific principles of development of the macro level logistics system related to improving its transit attractiveness for international freight carriers. The study also systematizes the model for determining the optimal location of logistics facilities. Particular attention is paid to the methodological basis of the analysis of transport terminals functioning as part of the logistics centers both in the stages of design and operation. The developed theoretical and methodological recommendations are universal and can be used in the design of the logistics infrastructure for various purposes and functions (including transport-logistics centers, trade-logistics centers etc.).